Structural validity of the physical fitness test battery - S. Palevych; V. Kirpenko; A. Piddubny; S. Bozhko; Z. Tzymbaliyk; Michael Anthonny Martinez Velez; Federico Anibal Martinez Velez; Jorge Armando Moreta Vinueza; Federico Antonio Martinez Leon (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Purpose: of the study was to examine the validity of the Army Combat Fitness Test tests on a sample of air defense personnel in the Ukrainian Ground Forces. Material and methods. The respondents to this study were 271 air defense servicemen of the ground forces aged 18 to 40 years (73 cadets of the Ivan Kozhedub Kharkiv National Air Force University and 198 military personnel). The structural validity was evaluated using a confirmatory factor analysis. Results. Compliance was achieved with the two-factor model obtained in the course of exploratory factor analysis, as evidenced by the following indixes: χ2 (8, Critical N = 465.29) = 10.43; χ2 / df = 1.303; Non-Normed Fit Index = 0.98; Normed Fit Index  = 0.97; Root Mean Square Error of Approximation = 0.035 (90 Percent Confidence Interval for Root Mean Square Error of Approximation  = (0.0; 0.088), Comparative Fit Index = 0.99. In addition, all factor loadings were statistically significant at the p < 0.01 level, that indicates that these two factors were well designed at every stage. Correlation between factors was weak, which confirms the discriminant validity of the test. The significant correlation found between the items and the overall test score confirmed the validity of the test. Conclusions. It was found that Army Combat Fitness Test is a suitable tool for evaluating the physical fitness condition of air defense personnel into the Ground Forces. The dilemmas about the possible use of Army Combat Fitness Test for all age groups of military personnel regardless of gender require further study.